Dependence on linkers' flexibility designed for benzenesulfonamides targeting discovery of novel hCA IX inhibitors as potent anticancer agents - Haytham O. Tawfik; Amany Belal; Mohammed A. S. Abourehab; Andrea Angeli; Alessandro Bonardi; Claudiu T. Supuran; Mervat H. El-Hamamsy (Taylor & Francis Group, 2022)
Herein we reported the design and synthesis of two series comprising twenty-two benzenesulfonamides that integrate the s-triazine moiety. Target compounds successfully suppressed the hCA IX, with IC50 ranging from 28.6 to 871 nM. Compounds 5d, 11b, 5b, and 7b were the most active analogues, which inhibited hCA IX isoform in the low nanomolar range (KI = 28.6, 31.9, 33.4, and 36.6 nM, respectively). Furthermore, they were assessed for their cytotoxic activity against a panel of 60 cancer cell lines following US-NCI protocol. According to five-dose assay, 13c showed significant anticancer activity than 5c with GI50-MID values of 25.08 and 189.01 µM, respectively. Additionally, 13c's effects on wound healing, cell cycle disruption, and apoptosis induction in NCI-H460 cancer cells were examined. Further, docking studies combined with molecular dynamic simulation showed a stable complex with high binding affinity of 5d to hCA IX, exploiting a favourable H-bond and lipophilic interactions.HIGHLIGHTSCarbonic anhydrase (CA) inhibitors comprising rigid and flexible linkers were developed.Compound 5d is the most potent CA IX inhibitor in the study (IC50: 28.6 nM).Compounds 5c and 13c displayed the greatest antiproliferative activity towards 60 cell lines.Compound 13c exposed constructive outcomes on normal cell lines, metastasis, and wound healing.Molecular docking and molecular dynamics (MDs) simulation was utilised to study binding mode.